Dengue infection changes the expressions of CD154 and CD148 in human platelets - Sayali Vedpathak; Sonali Palkar; AkhileshChandra Mishra; Vidya A Arankalle; Shubham Shrivastava (Virus Research)
Platelets are essential for hemostasis and vascular integrity. Platelets recognize dengue virus through the DC-SIGN receptor. Upon pathogen recognition, platelets rapidly modulate the expression of adhesion molecules to trigger immune cell interactions and regulate the immune response. In this study, we aimed to examine the expression levels of three molecules, CD151, CD154, and CD148 on platelets in dengue patients. A significantly increased expression of CD154 and reduced expression of CD148 was observed in dengue patients compared to healthy subjects (p < 0.0001). Moreover, a strong positive correlation between CD148 and CD41/CD61 (p < 0.0001) was noted in dengue patients. In summary, we demonstrated the altered expressions of CD154 and CD148 on platelets in dengue patients that may play a crucial role in dengue pathogenesis.